Women Judging Women: Gender Sensitivity in the Decisions of Divorce Cases of Indonesian Religious Courts - Asni, Asni; Muhammad Iqbal (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2025)
This article examines patterns of gender sensitivity in divorce rulings issued by female judges in Indonesian Religious Courts and analyzes the factors shaping their judicial reasoning. Using an empirical legal research design, the study combines document analysis of selected divorce decisions with in-depth interviews of female judges in several Religious Courts across Sulawesi. Guided by Alimatul Qibtiyah’s framework of gender sensitivity, the findings identify two dominant patterns: moderate and progressive. The moderate pattern is reflected in judicial reasoning that balances religious norms with social realities, emphasizing maṣlaḥah, harm prevention, and the psychological welfare of women and children within existing legal frameworks. The progressive pattern is evident in decisions that explicitly recognize domestic violence, economic neglect, and psychological abuse, and actively enforce women’s post-divorce rights, including nafkah ‘iddah, mut’ah, past maintenance, and child support, even in wife-initiated divorce cases. These patterns are influenced by factors such as gender-based empathy, professional experience, judicial training, and the implementation of Supreme Court regulations on gender-sensitive adjudication. This study highlights the role of female judges in advancing substantive justice in Islamic family law and underscores the importance of strengthening institutional support to ensure consistent protection of women’s rights in Religious Courts.